THE INFLUENCE OF PREDICT OBSERVE EXPLAIN WRITE TOWARDS OF CRITICAL THINKING SKILLS AND IN X DEGREE SMA N 2 SUKOHARJO IN ACADEMIC YEAR ON 2012/2013 - Puguh Karyanto, Hikmah Wartuti,datun, Sri Dwias (P Biologi FKIP UNS Surakarta, 2015)
This research aimed to find out whether or not there is an effect of Predict Observe Explain Write on the critical thinking ability of the X graders of SMA Negeri 2 Sukoharjo in academic year on 2012/2013..This study was a quasi experiment research. Posstet only nonequivalent control group design is used in this research. The population of research was all X grades of SMA Negeri 2 Sukoharjo in academic year 2012/2013 consisiting 285 students. Cluster sampling.is used to this research. The result of cluster sampling is choosen for X6 as experimental gruop and X7 as control group. Predict observe explain write model is applied in experimental group and conventional model is applied in control group. The data was collected by using critical thinking test, observastion sheet, and school documents. The data were analyzed by t-test.The results of this research shows that the mean of student?s capability of critical thinking in experiment class higher than control class, it was 70,41 for experiment class and 61,98 for control class. The result of hypothesis is analyzed by t-test and it gets significant value 0,000 (sig.<0,05), so the Predict Observe Explain Write model has effect toward student?s capability of critical thinking.This conclution is the application of Predict Observe Explain Write models has real effect toward critical thinking ability of X grade students at SMA Negeri 2 Sukoharjo in academic year on 2012/2013 . Keywords: Predict Observe Explain model, Think Talk Write strategy, Critical Thinking Ability